Corporate Digital Competencies for Digital Banking Innovation: Case Studies in Indonesian Banking Sector - Bambang Andri Irawan; Jann Hidajat Tjakraatmadja; Achmad Ghazali; Nur Budi Mulyono (Universitas Ahmad Dahlan, 2022)
Banking sector in Indonesia has enormous potential to grow. The large unbanked population, quick mobile & internet penetration, and advancement of digital technologies have propelled a fast-moving trend toward digital banking innovation. Banks and other financial service providers in Indonesia are anticipating this trend by preparing a roadmap to convert their business models, products, and services into full or partial digital financial propositions to meet the new customer’s expectations. This study investigates the required digital competencies at a corporate level that banking organizations need to prepare prior to stepping into digital transformation. Four Indonesian banks with different states of digital transformation have been selected as case studies for this qualitative study. This is an ongoing study, nevertheless, some initial findings and observations will be presented. While several previous research have discussed some parts of this study, the authors believe that no past research presented the whole set of corporate digital competencies especially in digital banking context. The outcome of this study is expected to be of value to the academics as well as to business.